Klotho and fibroblast growth factors 19 and 21 serum concentrations in children and adolescents with normal body weight and obesity and their associations with metabolic parameters - Anna Socha-Banasiak; Arkadiusz Michalak; Krzysztof Pacześ; Zuzanna Gaj; Wojciech Fendler; Anna Socha; Ewa Głowacka; Karolina Kapka; Violetta Gołąbek; Elżbieta Czkwianianc (BMC, 2020)
Abstract Background Fibroblast growth factor 19 (FGF19), fibroblast growth factor 21 (FGF21) and Klotho are regulators of energy homeostasis. However, in the pediatric population, the relationships between obesity, metabolic disorders and the aforementioned factors have not been clearly investigated. We analyzed the role of FGF19, FGF21 and Klotho protein in children with normal body weight as well as in overweight and obese subjects and explored their associations with insulin resistance (IR) and metabolic syndrome (MS) and its components. Methods This was a cross-sectional study conducted in a group of hospitalized children and adolescents. Laboratory investigations included serum analysis of FGF19, FGF21, and Klotho with ELISA kits as well as the analysis of the lipid profile and ALT serum concentrations. Moreover, each subject underwent an oral glucose tolerance test (OGTT) with fasting insulinemia measurement to detect glucose tolerance abnormalities and calculate the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) index. Furthermore, the clinical analysis included blood pressure measurement, body fat percentage estimation and assessment of the prevalence of MS and its components. Results The study was conducted with 174 children/adolescents aged 6-17 years with normal body weight (N = 48), obesity (N = 92) and overweight (N = 34). Klotho concentration was significantly higher in the obese children [median 168.6 pg/ml (90.2 to 375.9)]) than in the overweight [131.3 pg/ml (78.0 to 313.0)] and normal-body-weight subjects [116.6 pg/ml (38.5 to 163.9)] (p = 0.0334) and was also significantly higher in insulin-resistant children than in insulin-sensitive children [185.3 pg/ml (102.1 to 398.2) vs 132.6 pg/ml (63.9 to 275.6), p = 0.0283]. FGF21 was elevated in patients with MS compared to the FGF21 levels in other subjects [136.2 pg/ml (86.5 to 239.9) vs 82.6 pg/ml (41.8 to 152.4), p = 0.0286]. The multivariable model showed that FGF19 was an independent predictor of IR after adjusting for pubertal stage and BMI Z-score. Conclusions Klotho levels were associated with body weight status in children and adolescents. Moreover, Klotho, FGF19 and FGF21 concentrations correlated with IR status and/or components of MS.